(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: IVA examination is important for a woman of WUS because it can detect cervical cancer early. This method needs to be considered because it can be less noticed by WUS women themselves due to a lack of knowledge, husband’s support, distance to health facilities and also support from health workers. Purpose: The aim of this study was to determine the factors associated with IVA examination in WUS at the Sungai Pinang Health Center Methods: This research method uses a quantitative approach with the cross-sectional method, and a sample of 50 people. The research instrument used a questionnaire. Data analysis used univariate and bivariate chi square analysis. Results: The results of the study showed that there was a relationship between knowledge and the IVA examination for WUS at the Sungai Pinang Health Center. There is a relationship between husband’s support and WUS IVA examination at the Sungai Pinang Health Center. There is a relationship between the distance between health facilities and the IVA examination for WUS at the Sungai Pinang Health Center. There is a relationship between the support of health workers and the IVA examination for WUS at the Sungai Pinang Health Center. The support from health workers is the most dominant for IVA examinations for WUS women at the puskesmas. Conclusion: After doing research on the factor that is more influential is the support of health workers from all aspects so that WUS women can pay attention to early IVA examinations.